Management of lodging and yield maximization of wheat (Triticum aestivum L.) under Indo-gangetic plains - Dhiman Mukherjee (Annals of Agricultural Research, 2023)
An experiment was conducted during rabi season of 2018-19 and 2019-20 at District Seed Farm (AB Block), Kalyani under Bidhan Chandra Krishi Viswavidyalaya with the objective to maximize grain yield of wheat (Triticum aestivum L.) through various fertilization and lodging management in timely sown condition. Experiment was laid out in randomized block design, with twelve treatments consisting of four nutrient management options namely control, recommended fertilizer (150:60:40), two level of targeted yield of 6 (125:63:82) and 7 t/ha (140: 68: 101), with and without growth regulator. The crop growth retardant used were lihocin (chloremequat chloride) 0.2 % (GR 1) and lihocin 0.2 % + folicur 430 SC (tebuconazole) 0.1 % (GR 2). The crop growth retardants were used twice i.e. at first node (around 45 DAS) and flag leaf stage (around 80 DAS). Application of recommended NPK + GR1 and targeted yield -7 t/ha + GR2, which gave highest grain yield (4.6 t/ha) and showed parity with the recommended NPK + GR2 (4.4 t/ha) and targeted yield-7 t/ha + GR1 (4.3 t/ha), and statistically better to all other treatments. Chlormequat chloride (0.2%) + tebuconazole (0.1%) spray at 1st node and flag leaf development stage provided lower lodging score reflecting its reliability in lodging management. Higher net returns ( 51.8 ×103 /ha) and benefit:cost (B: C) ratio (2.10) exhibited with the recommended NPK + GR1 and was closely followed by the targeted yield-7 t/ha + GR2. It can be concluded that recommended dose of fertilizers with combined application of chlormequat chloride and tebuconazole plant growth regulators can be advocated as sustainable strategy for enhancing productivity and profitability of wheat cultivation in lodging prone area of Indo-Gangetic plain regions.